Systematic review of NTRK 1/2/3 fusion prevalence pan-cancer and across solid tumours - Sophie O’Haire; Fanny Franchini; Yoon-Jung Kang; Julia Steinberg; Karen Canfell; Jayesh Desai; Stephen Fox; Maarten IJzerman (Scientific Reports, 2023)
Abstract NTRK gene fusions are rare somatic mutations found across cancer types with promising targeted therapies emerging. Healthcare systems face significant challenges in integrating these treatments, with uncertainty in prevalence and optimal testing methods to identify eligible patients. We performed a systematic review of NTRK fusion prevalence to inform efficient diagnostic screening and scale of therapeutic uptake. We searched Medline, Embase and Cochrane databases on 31/03/2021. Inclusion criteria were studies reporting fusion rates in solid tumours, English language, post-2010 publication and minimum sample size. Critical appraisal was performed using a custom 11-item checklist. Rates were collated by cancer type and pooled if additional synthesis criteria were met. 160 studies were included, with estimates for 15 pan-cancer and 429 specific cancer types (63 paediatric). Adult pan-cancer estimates ranged 0.03–0.70%, with higher rates found in RNA-based assays. In common cancers, rates were consistently below 0.5%. Rare morphological subtypes, colorectal microsatellite instability, and driver mutation exclusion cancers had higher rates. Only 35.6% of extracted estimates used appropriate methods and sample size to identify NTRK fusions. NTRK fusion-positive cancers are rare and widely distributed across solid tumours. Small-scale, heterogeneous data confound prevalence prediction. Further large-scale, standardised genomic data are needed to characterise NTRK fusion epidemiology.